2022
DOI: 10.3390/cimb44060180
|View full text |Cite
|
Sign up to set email alerts
|

Apigetrin Abrogates Lipopolysaccharide-Induced Inflammation in L6 Skeletal Muscle Cells through NF-κB/MAPK Signaling Pathways

Abstract: Apigetrin is a glycosidic flavonoid derived from Teucrium gnaphalodes that has a wide range of biological activities, including antioxidant, anti-inflammatory, and anticancer. Inflammation is a kind of defense mechanism in the body. Flavonoids are natural phytochemicals that exert anti-inflammatory effects in numerous cells. In the present study, we investigated the anti-inflammatory effect of apigetrin and its underlying mechanism of activity in skeletal muscle cells (L6). The determination of cytotoxicity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…4). Consistent with our data, apigetrin has been reported to lower TNF-α, IL-1β, and IL-6 production and mRNA expression in LPS-stimulated various cells [16, 17,51] and in mice with acute otitis media [19]. Similarly to our model, it has been reported that apigetrin inhibits IL-1α and TGF-β production induced by recombinant spike protein of SARS-CoV-2-stimulated RAW 264.7 cells [52].…”
Section: Discussionsupporting
confidence: 91%
“…4). Consistent with our data, apigetrin has been reported to lower TNF-α, IL-1β, and IL-6 production and mRNA expression in LPS-stimulated various cells [16, 17,51] and in mice with acute otitis media [19]. Similarly to our model, it has been reported that apigetrin inhibits IL-1α and TGF-β production induced by recombinant spike protein of SARS-CoV-2-stimulated RAW 264.7 cells [52].…”
Section: Discussionsupporting
confidence: 91%
“…After internalization of the drug‐loaded nanoparticles, IL‐1β‐treated IVD tissue showed a dramatic reduction in many inflammatory mediators (IL‐6, IL‐8, and PGE2), while remodeled ECM manifested by upregulation of ECM proteins (Collagen II and Aggrecan) and downregulation of matrix degrading enzymes (MMP1 and MMP3). 54 API shows excellent anti‐inflammatory effects on various cell types, including skeletal muscle cells, 55 microglia, 24 , 56 and adipocytes, 57 which makes it a promising treatment for inflammation‐related diseases. Similarly, our results demonstrated that API significantly downregulated proinflammatory factors, which may further reduce catabolic activity while increasing anabolism in IL‐1β‐stimulated NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is an important factor that causes skeletal muscle atrophy [14]. Proinflammatory cytokines can trigger muscle atrophy mediated by the activating ubiquitinproteasome and NF-κB/MAPK signaling pathways [26,27]. MAPKs including ERK, c-Jun N-terminal kinase, and p38 regulate MAFbx and MuRF1 expression of muscles under oxidative stress and inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%